2015
DOI: 10.3109/15376516.2015.1020182
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of pesticides and the immune dysregulation: mechanisms, evidence and consequences

Abstract: Nowadays, in many communities, there is a growing concern about possible adverse effects of pesticides on human health. Reports indicate that during environmental or occupational exposure, pesticides can exert some intense adverse effects on human health through transient or permanent alteration of the immune system. There is evidence on the relation between pesticide-induced immune alteration and prevalence of diseases associated with alterations of the immune response. In the present study, direct immunotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(69 citation statements)
references
References 205 publications
0
65
0
4
Order By: Relevance
“…Eder et al (2008) and Shen et al (2018) reported the immunotoxic effect of pyrethroid insecticides in fish. Mokarizadeh et al (2015) investigated the immunotoxic effects of pesticides specially pyrethroids in human and reported that the immune response to certain mitogens is either decreased, delayed or not shown at all.…”
Section: Discussionmentioning
confidence: 99%
“…Eder et al (2008) and Shen et al (2018) reported the immunotoxic effect of pyrethroid insecticides in fish. Mokarizadeh et al (2015) investigated the immunotoxic effects of pesticides specially pyrethroids in human and reported that the immune response to certain mitogens is either decreased, delayed or not shown at all.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have provided a critical foundation from which effects related to exogenous chemicals can be compared, and crucial evidence showing that activation of the maternal immune system can alter fetal brain cytokines [143, 147]. Various exogenous chemicals, such as phenols (e.g., BPA) and pesticides (e.g., CPF), have been shown to disrupt immune cells and the cytokines they produce [148, 149], including during stages of development [150, 151], with both increases and decreases in inflammatory markers observed. There is some evidence of altered neuroimmune response following exposure to exogenous chemicals; however, we are just beginning to further elucidate these mechanisms and assess other immune-related signaling molecules, such as chemokines.…”
Section: Mechanisms Of Developmental Neurotoxicitymentioning
confidence: 99%
“…Although cell mechanisms related to the development of cancers induced by pesticide exposure are not fully understood, it is supposed that the pathways may include abnormal immune response, oxidative stress, DNA damage, and chromosome aberration . The International Agency for Research on Cancer (IARC) had included some pesticides in the list of carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although cell mechanisms related to the development of cancers induced by pesticide exposure are not fully understood, it is supposed that the pathways may include abnormal immune response, oxidative stress, DNA damage, and chromosome aberration. 7 The International Agency for Research on Cancer (IARC) had included some pesticides in the list of carcinogens. The insecticides pentachlorophenol and lindane were evaluated as carcinogen to humans (Group 1), with epidemiological data showing sufficient evidence for an increased risk for non-Hodgkin lymphoma and multiple myeloma.…”
mentioning
confidence: 99%